Mean platelet volume as short-term follow-up biomarker in children with celiac disease - Ramachandran, Mohanaraj; Agarwal, Anurag; Ravi, R N Mandal; Rajeshwari, K; Lomash, Avinash; Kapoor, Seema (Indian Journal of Child Health, 2017)
Objective: To assess the mean platelet volume (MPV) as a short-term follow-up biomarker in celiac disease (CD) and to compare it with anti-tissue transglutaminase antibody (TTGA) assay in Indian children. Material and Methods: Newly diagnosed 35 children aged <12 years who were positive for TTGA and further confirmed by intestinal biopsy with histological Grade 2 and 3 based on modified Marsh Classification were enrolled. TTGA, MPV, and clinical parameters were assessed at enrollment and after 3 months of gluten free diet (GFD). Results: Short stature (94.3%) and diarrhea (80%) were the most common presenting features. 33 (94.3%) children were found to have anemia. MPV reduced significantly from 9.28±1.88 fl to 8.55±1.10 fl after 3 months of GFD, (p<0.001). The mean TTG level reduced from 166.80±59.23 U/ml to 86.45±39.67 U/ml (p<0.001) after 3 months of GFD. Conclusion: MPV is one of the biomarkers that can be used to monitor dietary transgressions in CD in short term.